Contribuições a uma teoria da democracia digital como suporte à formulação de políticas públicas - Rothberg, Danilo [UNESP] (My University, 2010)
Under the realm of the Brazilian federal government, online public consultations have been expanded as a means of shared formulation of policies of many government sectors, especially science and technology. However, despite the fast multiplication of those instruments of political participation in the last few years, there can be resistances to their advance. So it is convenient to clarify the domain in which the strengthening of the electronic means of participation can be supported in the Latin American context. This paper proposes contributions to a theory of digital democracy which might sustain efforts to the development of that field. Attention is drawn to the political conception of justice according to Rawls and Habermas’ theory of discourse ethics, which can bear the notion that individuals and groups should, in liberal-democratic societies, cooperatively act in order to value their political liberty in agreements about goals and priorities of the manners of promoting justice and reducing inequalities.

No âmbito do governo federal brasileiro, as consultas públicas online têm ganhado espaço como meio de formulação compartilhada de políticas públicas de diversos setores de governo, especialmente ciência e tecnologia. Mas, a despeito da rápida multiplicação desses instrumentos de participação política nos últimos anos, podem existir resistências ao seu avanço. Daí ser conveniente clarear o terreno em que se pode defender o fortalecimento dos meios participativos eletrônicos no contexto latino-americano. Este artigo propõe contribuições a uma teoria da democracia digital que fundamente esforços de desenvolvimento da área. O enfoque se dá sobre a concepção política da justiça segundo Rawls e a ética do discurso de Habermas, que podem sustentar a noção de que indivíduos e setores devem, em sociedades democrático-liberais, agir cooperativamente para fazer valer sua liberdade política em acordos sobre diretrizes e prioridades das formas de promoção de justiça e de redução de desigualdades.
Keywords: Online public consultations; Digital democracy; Science and technology public policies; Consultas públicas online; Democracia digital; Políticas públicas de ciência e tecnologia